Spectrum of Inherited Hemoglobin Disorder in patients presenting for Hb Electrophoresis: A Single Center Study in District Dera Ismail Khan - Zahid Ullah, Rehana Rasool, Nighat Aziz, Rahila Bano, Saima Bashir, Sarah Arif Ali, Aamir Ali Khattak, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hemoglobinopathies remains an important public health Problem for developing countries like Pakistan as it has been associated with high morbidity and mortality rates. The objective of this study was to know the frequency distribution of various hemoglobinopathies in ethnically and geographically diverse population of Dera Ismail Khan of Pakistan referred for Hemoglobin electrophoresis. Methods: This cross sectional study was conducted at Pathology department of Gomal Medical College, Dera Ismail Khan, from January 2017 to December 2021. About 3 ml of venous anticoagulatedblood specimen were collected from suspects for Complete Blood Count, Sickling Test and hemoglobin electrophoresis. Result: Of the 538 cases, 219(40.7%) were found normal and 319(59.3%) were found positive for abnormal hemoglobin disorder. Among positive samples 317(58.9%) were male and 221(41.1%) were female. BetaThalassemia was the most common hemoglobinopathyobserved in 194(60.8%) followed by sickle cell 105(32.9%), hemoglobin E, D and C were found in 9 (2.8%), 4(1.2) and 2(0.6%) respectively. Frequency of Beta Thalassemia is quite high in Balochtribe followed by Mehsud and Marwat. Sickle gene was more prevalent in Sherani followed byBhatni and Ustrana. Conclusion: Beta Thalassemia and Sickle cell are the two most common hemoglobin disorders found in our set up. Mass screening with genetic counselingand education should be initiated to reduce disease burden. Keywords: Electrophoresis, Hemoglobinopathies, Dera Ismail Khan.